2023
DOI: 10.1155/2023/4444869
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Prognostic Signature Based on the Lysine Crotonylation Regulators in Head and Neck Squamous Cell Carcinoma

Abstract: Background. Lysine crotonylation (Kcr) is a newly identified posttranslational modification type regulated by various enzymes and coenzymes, including lysine crotonyltransferase, lysine decrotonylase, and binding proteins. However, the role of Kcr regulators in head and neck squamous cell carcinoma (HNSCC) remains unknown. The aim of this study was to establish and validate a Kcr-related prognostic signature of HNSCC and to assess the clinical predictive value of this signature. Methods. The mRNA expression pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Moreover, it was also reported that most Kcr regulators, including DPF2, KAT2B, and HDAC2–3, were significantly dysregulated in patients with head and neck squamous cell carcinoma (HNSCC); this observation positively correlated with lymph-node metastasis, T stage, and histologic grade [ 126 ]. Specifically, KAT2B decreased in the advanced compared with the early T stage ( p = 0.0016), disclosing the negative correlation between KAT2B and the T stage.…”
Section: Roles Of Novel Acylations In Tumor Metastasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it was also reported that most Kcr regulators, including DPF2, KAT2B, and HDAC2–3, were significantly dysregulated in patients with head and neck squamous cell carcinoma (HNSCC); this observation positively correlated with lymph-node metastasis, T stage, and histologic grade [ 126 ]. Specifically, KAT2B decreased in the advanced compared with the early T stage ( p = 0.0016), disclosing the negative correlation between KAT2B and the T stage.…”
Section: Roles Of Novel Acylations In Tumor Metastasesmentioning
confidence: 99%
“…SUCLG2 is estimated to be a biomarker candidate that can effectively differentiate between follicular adenoma and carcinoma with 75% sensitivity and 80% specificity, depending on a specific cutoff score extrapolated from the intensity and percentage of immunohistochemistry (IHC) staining [ 125 ]. Based on Kcr regulators, a nine-gene signature, including DPF2, HDAC2, and HDAC3, was established and validated as an independent factor for prognosis in patients with HNSCC; this could effectively distinguish patients into low- and high-risk groups depending on the difference in OS using the GEO-HNSCC dataset ( p = 0.023) [ 126 ]. Univariate analysis of training cohorts revealed that the risk characteristics obtained from the nine-gene regulators were significantly associated with OS ( p < 0.001, HR 4.175, 95% CI 2.573–6.776); the nine-gene risk assessment from the multivariate analysis further verified their potential as independent prognostic factors ( p < 0.001, HR 3.500, 95% CI 2.178–5.625) [ 126 ].…”
Section: Clinical Significancementioning
confidence: 99%
See 1 more Smart Citation
“…This modification is catalyzed by a family of enzymes called histone crotonyltransferases (KAT5/8), which use crotonyl-CoA as a cosubstrate. Histone crotonylation can activate or repress the transcription of specific genes in HNSCC by altering chromatin structure, thereby influencing disease progression ( 38 ). Through sequencing and enrichment analysis, it has been found that histone malonylation of HSP90AB1 mediates the onset and progression of oral squamous cell carcinoma ( 39 ).…”
Section: Novel Histone Modifications In Hnsccmentioning
confidence: 99%